2016
DOI: 10.1007/s10682-016-9827-6
|View full text |Cite
|
Sign up to set email alerts
|

Linking trophic interactions to plasticity in thermal sensitivity of geographically separated populations of a herbivore

Abstract: The ability of species to tolerate a warming climate has important implications for ecological functioning. Theory and empirical synthesis suggest species adapted to more thermally variable climates are more capable of acclimating to rising temperatures, and are therefore characterized by greater phenotypic plasticity, than species adapted to less thermally variable environments. But this pattern has not been extensively evaluated for populations within a species that may inhabit different parts of a thermal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…The low temperature (15°C) was chosen because it represents the lower end of thermal conditions M. femurubrum grasshopper populations could experience for prolonged periods during the summer growing season in the field (Rosenblatt et al. ). The middle temperature (25°C) approximates average summer growing temperatures that field populations could experience (Rosenblatt et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low temperature (15°C) was chosen because it represents the lower end of thermal conditions M. femurubrum grasshopper populations could experience for prolonged periods during the summer growing season in the field (Rosenblatt et al. ). The middle temperature (25°C) approximates average summer growing temperatures that field populations could experience (Rosenblatt et al.…”
Section: Methodsmentioning
confidence: 99%
“…The middle temperature (25°C) approximates average summer growing temperatures that field populations could experience (Rosenblatt et al. ). The high temperature (35°C) represents upper extreme levels that field populations could experience (Rosenblatt et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These targets may also change as a function of environmental conditions (Rosenblatt et al. , Schmitz et al. ), so it is not surprising that grasshoppers shift their diet in the presence of predators.…”
Section: Discussionmentioning
confidence: 99%
“…While other factors including temperature may elevate metabolism and alter diet (Rosenblatt et al. , Schmitz et al. ), most studies have found that dietary preferences of grasshoppers are invariant across temperatures and driven entirely by predation risk (Barton and Schmitz , Barton et al.…”
Section: Introductionmentioning
confidence: 99%